Ethno-Medico-Botanical observations on some wild tuberous plants of Kinwat Forest, Nanded - Shinde SR (International Journal of Life Sciences, 2015)
An extensive survey of Kinwat forest during 2009-2010 related to wild tuberous medicinal plants was conducted. It has been observed that, wild tuberous plant species are in traditional use by local tribes to treat various human diseases. The present paper provides the medicinal uses of the few less-known wild tuberous plants.